2016
DOI: 10.1021/acsbiomaterials.6b00564
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Modulation of Tropoelastin Structure and Assembly

Abstract: Tropoelastin, as the monomer unit of elastin, assembles into elastic fibers that impart strength and resilience to elastic tissues. Tropoelastin is also widely used to manufacture versatile materials with specific mechanical and biological properties. The assembly of tropoelastin into elastic fibers or biomaterials is crucially influenced by key submolecular regions and specific residues within these domains. In this work, we identify the functional contributions of two rarely occurring negatively charged resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 79 publications
1
17
0
Order By: Relevance
“…They observed higher sarcomeric organization and differentiation at day 7 of culture on collagen coated aligned fibers and aligned fiber scaffolds compared to random fiber scaffolds. [105,106] In another example of biomimetic muscle bundle fabrication, Kim and colleagues fabricated a microfibrous PCL bundle by using a melt-printing system to print at 85 °C a PVA/PCL (ratio 3:7) solution with a 350 µm nozzle at a speed of 10 mm s −1 and a pneumatic pressure of 250 kPa. The sacrificial PVA was removed in water after 24 h, then the PCL structure was coated with 0.5% collagen crosslinked by 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide (EDC) for 30 min, and the scaffold was freeze dried for 12 h. Due to the microfibrillation of PVA and the leaching of PVA from the mixture of PVA/PC, the scaffold had a surface with aligned microfibrous pattern and a section allowing cell penetration between the microfibers (Figure 6a).…”
Section: D Printing and Bioprinting In Skeletal Muscle Tissue Enginementioning
confidence: 99%
“…They observed higher sarcomeric organization and differentiation at day 7 of culture on collagen coated aligned fibers and aligned fiber scaffolds compared to random fiber scaffolds. [105,106] In another example of biomimetic muscle bundle fabrication, Kim and colleagues fabricated a microfibrous PCL bundle by using a melt-printing system to print at 85 °C a PVA/PCL (ratio 3:7) solution with a 350 µm nozzle at a speed of 10 mm s −1 and a pneumatic pressure of 250 kPa. The sacrificial PVA was removed in water after 24 h, then the PCL structure was coated with 0.5% collagen crosslinked by 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide (EDC) for 30 min, and the scaffold was freeze dried for 12 h. Due to the microfibrillation of PVA and the leaching of PVA from the mixture of PVA/PC, the scaffold had a surface with aligned microfibrous pattern and a section allowing cell penetration between the microfibers (Figure 6a).…”
Section: D Printing and Bioprinting In Skeletal Muscle Tissue Enginementioning
confidence: 99%
“…[76,85] Indeed, local mutations in the sequence result in global modifications that may disrupt the shape of the molecule and potentially alter the exposure of the bioactive motifs and the final functional assembly into the elastic fiber. [86][87][88] The N-terminal coil region provides elastic properties to tropoelastin in its uncrosslinked state and is associated with the regulation of self-assembly and crosslinking during elastogenesis. [84] The hinge and bridge regions are highly flexible and contribute to elastic fiber assembly and mechanical coupling.…”
Section: Structural Propertiesmentioning
confidence: 99%
“…[ 76,85 ] Indeed, local mutations in the sequence result in global modifications that may disrupt the shape of the molecule and potentially alter the exposure of the bioactive motifs and the final functional assembly into the elastic fiber. [ 86–88 ]…”
Section: The Realm Of Elastinmentioning
confidence: 99%
“…It has been shown that the insertion or deletion of TE domains or the mutation of certain amino acid residues affects diverse mechanisms associated with the assembly of TE monomers into a polymeric network such as coacervation and cross‐linking processes as well as the resultant mechanical properties. This suggests that variations in the TE sequence allow tissue‐specific alterations in elastin properties or are responsible for abnormal fiber formation under pathological conditions …”
Section: Tropoelastin Domain Structure and Expressionmentioning
confidence: 99%
“…This suggests that variations in the TE sequence allow tissue-specific alterations in elastin properties or are responsible for abnormal fiber formation under pathological conditions. [15][16][17] TE's sequence is highly repetitive and about 80% are composed of the four amino acids Gly, Ala, Val, and Pro. The precursor has alternating hydrophobic and more hydrophilic domains, which are encoded by individual exons, so that the domain structure of the protein is reflected in the exon organization of its gene.…”
Section: Introductionmentioning
confidence: 99%